Advances in the Protective Mechanism of NO, H2S, and H2 in Myocardial Ischemic Injury - Wang, Wei-lu; Ge, Tian-yu; Chen, Xu; Mao, Yicheng; Zhu, Yi-zhun (Frontiers in Cardiovascular Medicine, 2020)
Myocardial ischemic injury is among the top 10 leading causes of death from cardiovascular diseases worldwide. Myocardial ischemia is caused mainly by coronary artery occlusion or obstruction. It usually occurs when the heart is insufficiently perfused, oxygen supply to the myocardium is reduced, and energy metabolism in the myocardium is abnormal. Pathologically, myocardial ischemic injury generates a large number of inflammatory cells, thus inducing a state of oxidative stress. This sharp reduction in the number of normal cells as a result of apoptosis leads to organ and tissue damage, which can be lifethreatening. Therefore, effective methods for the treatment of myocardial ischemic injury and clarification of the underlying mechanisms are urgently required. Gaseous signaling molecules, such as NO, H2S, H2, and combined gas donors, have gradually become a focus of research. Gaseous signaling molecules have shown anti-apoptotic, anti-oxidative and antiinflammatory effects as potential therapeutic agents for myocardial ischemic injury in a large number of studies. In this review, we summarize and discuss the mechanism underlying the protective effect of gaseous signaling molecules on myocardial ischemic injury.